Skills and Practices of European Orthopedic Nurses in Empowering Patient Education - Klemetti, Seija; Ingadottir, Brynja; Katajisto, Jouko; Lemonidou, Chryssoula; Papastavrou, Evridiki; Valkeapää, Kirsi; Zabalegui, Adelaida; Leino-Kilpi, Helena (My University, 2018)
Purpose: This study provides an overview of the self-defined skills and practices of European orthopedic nurses in empowering patient education. Nurses themselves have highlighted the necessity to enhance their own skills, but possibilities for further education have been limited. Methods: The data (n = 317 nurses) from a structured survey were collected during the years 2009-2012 in seven European countries with an EPNURSE-questionnaire (Empowering Patient Education from the point of view of Nurses). Results: Nurses considered patient education as an important part of their work and evaluated their own skills as good. However, their patient education practices were based more on practices on their ward and their own experience than on further education or evidence-based knowledge. On the other hand, lack of time for patient education and experienced overload were the major barriers experienced by nurses. Implications for Practice: Further education of orthopedic nurses in empowering evidence-based patient education is highly needed. Nurse leaders need to acknowledge the strong need for supporting nurses within clinical practice, improve their evidence-based knowledge and support practices that prioritize patient education within the hospital environment. Further international collaboration in nursing research and health-care organizations is desirable to reach these patient educational goals in clinical nursing practice.
Keywords: Empowerment; Nursing; Patient education; Practices; Skills